Tuning thermal stability and mechanical sensitivity of polynitro compounds via integrating energetic ionic salts - Mei-Qi Xu; Wen-Shuai Dong; Zu-Jia Lu; Cong Li; Chao Zhang; Bin-Shan Zhao; Deng-Ke Li; Feng-Yuan Tian; Qi-Yao Yu; Jian-Guo Zhang (Energetic Materials Frontiers)
Polynitro energetic compounds are a class of oxidant-rich energetic materials, playing a significant role in the field of solid propellants. Generally, an increase in the number of nitro groups present in these compounds is associated with a decrease in thermal stability, while simultaneously resulting in an enhancement of mechanical sensitivity. The incorporation of nitrogen-containing organic bases in the synthesis of polynitro energetic ionic salts facilitates a more uniform distribution of charge and promotes the formation of both intramolecular and intermolecular hydrogen bonds. This strategy effectively enhances the thermal stability of HEDMs while decreasing their mechanical sensitivity. In this study, two polynitro nitrogen-containing organic salts based on the triazole framework, namely ammonium salt (4) and hydroxylamine salt (5), were designed and synthesized. Comprehensive characterization revealed that both 4 and 5 exhibited excellent detonation performance (D: 8220–8959 m⋅s−1), good thermal stability (Td: 154–175°C), and low mechanical sensitivity (IS: 30–32 J; FS: 240–288 N). Therefore, nitrogen-containing organic salts enhance the overall performance of polynitro energetic compounds, offering significant advantages in terms of safety and application potential.